Occurrence of aragonite corrosive water in the North Yellow Sea, near the Yalu River estuary, during a summer flood. (5th December 2015) - Zhai, Wei-Dong; Zang, Kun-Peng; Huo, Cheng; Zheng, Nan; Xu, Xue-Mei
Abstract: To understand seawater CaCO3 saturation state (Ωarag for aragonite and Ωcal for calcite) dynamics in river-dominated ocean margins, we investigated the carbonate system and ancillary parameters in the North Yellow Sea, near the Yalu River estuary, during and after a summer flood (August and September 2013, respectively). During the flood period, nearshore Ωarag ranged from 0.76 to 1.61 and Ωcal ranged from 1.22 to 2.53. Aragonite undersaturation values were associated with quite low salinity of 14.58–25.18 and a broad dissolved oxygen saturation range from 58% to 102%. A week after the flood period, aragonite undersaturated waters together with the estuarine plumes disappeared. Based on field data analyses and simplified model simulation, we suggest that net community respiration/remineralization and the dilution of riverine water discharge both contributed to the low CaCO3 saturation states. Graphical abstract: Highlights: The seawater carbonate system was investigated near the Yalu River estuary. Shallow-water aragonite undersaturation occurred in the Chinese coastal zone. Both respiration and dilution contributed to the low CaCO3 saturation states. Combined effects of the two contributors were quantificationally analyzed.